MENINGKATKAN KETERAMPILAN MENEMPEL MELALUI PERMAINAN KOLASE DARI BAHAN ALAM ANAK TUNAGRAHITA RINGAN - Afri yanti (Universitas Negeri Padang, 2012)
This study originated from the fact that school children with impaired Tunagrahita Lightweight stick skills. From the observation of children in late stick skills of the others, of paper taped to the child out of the pattern and cleanliness in the attached picture is very less. Children also experienced problems with the fine motor skills such as folding paper as great difficulty, difficulty buttoning clothes. . The purpose of this study was to determine whether the game collage of natural ingredients can improve stick skills mild mental retardation in children class II / C at SDN 35 (SDLB) Painan north. This study used experimental approach in the form of Single Subject Research (SSR) with a research design using AB. The results of this study indicate that children stick skills Tunagrahita Lightweight X increases. Initially the children are able to stick to the green bean seeds eight to 12 times during the five observations. Having given intervention with collage game and eventually increased to 14 to 24 green beans consistently for eight observations, and be able to stick to fruit sago initially five to nine pieces of sago for four times after a given observation and intervention through the game and eventually rose to collage 10 to 18 pieces of sago consistently for eight observations. Thus, the game is a collage of natural material mild mental retardation in children can be effective to improve the skills of children in the stick, so the hypothesis put forward previously acceptable. This means that the game can raise the stick collage in children Tunagrahita Lightweight class II / C. Results from this study are expected to be useful for teachers and further research and can serve as guidelines to continue to use the game collages from natural materials to improve stick skills mild mental retardation in children future